2017
DOI: 10.1016/j.stemcr.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic ALS Astrocytes Induce Neuronal Degeneration In Vivo

Abstract: SummaryAstrocytes from familial amyotrophic lateral sclerosis (ALS) patients or transgenic mice are toxic specifically to motor neurons (MNs). It is not known if astrocytes from sporadic ALS (sALS) patients cause MN degeneration in vivo and whether the effect is specific to MNs. By transplanting spinal neural progenitors, derived from sALS and healthy induced pluripotent stem cells (iPSCs), into the cervical spinal cord of adult SCID mice for 9 months, we found that differentiated human astrocytes were present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 41 publications
3
96
0
Order By: Relevance
“…; Qian et al . ), to our knowledge, no electrophysiological investigations have been reported in sporadic forms. Because mutations account for less than 20% ALS cases, and given the disappointing results of therapeutic translation (from mice to humans), there is a possibility that hypoexcitability is a specific feature of familial forms and animal models.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…; Qian et al . ), to our knowledge, no electrophysiological investigations have been reported in sporadic forms. Because mutations account for less than 20% ALS cases, and given the disappointing results of therapeutic translation (from mice to humans), there is a possibility that hypoexcitability is a specific feature of familial forms and animal models.…”
Section: Introductionmentioning
confidence: 76%
“…in motoneurons disconnected from the motor network). Furthermore, although motoneurons or astrocytes derived from sporadic ALS iPSCs exhibit similar characteristics to those derived from familial forms (Burkhardt et al 2013;Qian et al 2017), to our knowledge, no electrophysiological investigations have been reported in sporadic forms. Because mutations account for less than 20% ALS cases, and given the disappointing results of therapeutic translation (from mice to humans), there is a possibility that hypoexcitability is a specific feature of familial forms and animal models.…”
Section: Introductionmentioning
confidence: 86%
“…The increase in HSPB was not due to an increase in astrocyte numbers per se as GFAP and ALDH1 levels did not differ from controls. Astrocytes in ALS contain inclusions and exhibit an altered phenotype, likely contributing to motor neuron death . As astrogliosis may be a physiological response necessary for tissue repair as well as playing a pathogenic role, the actual role that HSPBs play in astrocytes during ALS remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was also shown that astrocyte-like cells, isolated from postmortem spinal cord of sporadic ALS patients, highly expressed inflammatory mediators and caused neuronal toxicity when cocultured with ES derived neurons (Haidet-Phillips et al, 2011). When astrocytes derived from sporadic ALS patients were transplanted in the spinal cord of healthy mice, these showed lower presynaptic connections and impaired neuromuscular junctions (Kelley et al, 2018;Qian et al, 2017).…”
Section: Astrocytes In Alsmentioning
confidence: 99%